The Effectiveness of Online Teaching and Learning During Covid-19 Pandemic: Teacher’s/ Learner’s Perspective at Western Philippines University - Laarnie Mipa-Narrazid; Jergen Jel C. Labaria (Genius Journals, 2021)
The whole educational system from elementary to tertiary level has been collapsed during the lockdown period of the novel coronavirus disease 2019 (COVID-19) not only in the Philippines but across the globe. This study is a portrayal of online teaching-learning modes used in Master in Education and Management at Western Philippines University for the teaching-learning process. This study was conducted to determine the effectiveness of online teaching learning among teachers/learners of Western Philippines University taking Master in Education. Specifically, it sought to answer the following questions: (1) what are the various forms of online teaching-learning mode adopted during Covid-19 pandemic? (2) What are the perceptions of teachers/learners on online teaching-learning during Covid-19 pandemic? (3) What are the challenges faced by the teachers/learners in adapting the online teaching-learning process during Covid-19 pandemic? The descriptive method of research was used in this study. The questionnaire composed of two parts was administered to the 41 respondents of which 7 are males and 34 females. Based on the following findings, the perceptions of teachers/learners was based on their experiences during online teaching-learning modes: first, it’s difficult to get an immediate feedback on what was being taught, second, lack of direct contact with learners, third, possible distractions from other family during online lectures may occur, fourth, they prefer to have a training on conducting online lectures, and fifth, poor internet connection is their major problem they’ve encountered. From the conclusion of the study, the recommendations are proposed: (1) the governments must ensure the availability of reliable communication tools, high quality digital academic experience, and promote technology enabled learning for teachers and learners to bridge the disparities originated in the education system before and after COVID-19 catastrophe which is also inevitably necessitated for uninterrupted learning. (2) Few steps should be accounted in the wake of this pandemic; to develop such a curriculum that reflects the perceptible change in the content knowledge and learning experience of teachers/learners as well as enable them to think critically, (3) Teachers/learners must attend different trainings about computer or Information Technology for them to have enough knowledge on how to use and manage it, (4) Different telecommunications companies, like; Smart, Globe, Talk and Text, Sun and many more must provide a good services to their consumers for them to have a good access into internet, and (5) Teachers/learners must have a huge patience, determination and perseverance to conquer those challenges faced during online teaching and learning modes. The value of this paper is to draw a holistic picture of on-going online teaching-learning activities during the pandemic period including establishing the linkage between change management process and online teaching-learning process in education system amid the COVID-19 outbreak so as to overcome the persisting academic disturbance and consequently ensure the resumption of educational activities and discourses as a normal course of procedure in the education system.
Keywords: COVID-19; outbreak; perception; pandemic period